Ricardo's economics : a general equilibrium theory of distribution and growth - Morishima, Michio (Cambridge University Press, 1989)
Together with "Marx's Economics" and "Walras' Economics" this book completes a sequence of titles by Professor Morishima on the first generation of scientific economists. As with his treatment of Marx and Walras, the author's assessment of Ricardo differs substantially from established views